Pendekatan manajerial bidan dalam penerapan asuhan: A literature review - Aulia, Devy Lestari Nurul; Anjani, Arum Dwi; Windari, Anggun; Romania, Dwi; Octafera, Nasywa Putri; Novira, Selvi; Syaira, Marchellya; Zahra, Ikqlima; Kurniasari, Zeti; Susanti, Nora Elvi; Tambunan, Lidia Martianna (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The identified phenomenon is that midwives are required to provide evidence-based, standardized, and professional care to ensure the health and quality of life of infants and mothers. Improving the quality of midwifery services can be achieved through strategic steps, including a midwifery managerial approach to midwifery care. This managerial approach can provide clear direction, especially in the context of midwifery services, such as practice in hospitals, community health centers, or independent practice. Purpose: To examine the midwifery managerial approach to midwifery care. Method: A literature review and search were conducted using databases such as Google Scholar Garuda (Garba Digital Reference), PubMed, and ResearchGate, using keywords such as